Knowledge graph and semantic computing : language, knowledge, and intelligence : second China Conference, CCKS 2017, Chengdu, China, August 26-29, 2017, Revised selected papers /: language, knowledge, and intelligence : second China Conference, CCKS 2017, Chengdu, China, August 26-29, 2017, Revised selected papers. (2017) - Unknown
No abstract available